1985
DOI: 10.1002/bjs.1800720511
|View full text |Cite
|
Sign up to set email alerts
|

Probability of false negative nodal staging in conjunction with partial axillary dissection in breast cancer

Abstract: There is a risk of overlooking lymph node metastases and thereby contributing to inaccurate nodal staging when performing partial axillary dissection in conjunction with total mastectomy in female breast cancer. The Danish Breast Cancer Cooperative Group (DBCG) analysed this risk in a prospective nation-wide adjuvant trial dealing with primary operable breast carcinoma. The series comprised 3114 patients, initially found to have lymph node negative axillae, followed for a median of 24 months (quartiles 12-40).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
7

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 15 publications
3
35
0
7
Order By: Relevance
“…For number of excised lymph nodes /?=-0.21, which yields a factor of 0.81 in the intensity. The intensity thus drops with growing number of excised lymph nodes, as also observed earlier (13). Menopausal status was not observed to have any effect on the recurrence-free survival.…”
Section: Tests In the Modelsupporting
confidence: 79%
“…For number of excised lymph nodes /?=-0.21, which yields a factor of 0.81 in the intensity. The intensity thus drops with growing number of excised lymph nodes, as also observed earlier (13). Menopausal status was not observed to have any effect on the recurrence-free survival.…”
Section: Tests In the Modelsupporting
confidence: 79%
“…We could observe no axillary recurrence in 200 patients with a median follow-up of 36 months after SLNB only. If we had missed the true SLN and if we had an unknown false-negative rate, we should have observed 2 -12% of patients (Kjaergaard et al, 1985;Senofsky et al, 1991) with axillary recurrences, which were 4 -24 patients. All of our patients were SLN negative in frozen sections, H&E and IHC staining.…”
Section: Discussionmentioning
confidence: 98%
“…The importance of axillary lymph node status in determining prognosis in breast cancer and helping in the planning of adjuvant therapy is widely accepted. Moreover, axillary clearance contributes to the local control of the disease and reduces the incidence of axillary recurrence (Kjaergaard et al, 1985;Benson and Thorogood, 1986;Hayward and Caleffi, 1987). Harris and Osteen (1985) have reported improved survival in patients following axillary surgery, although most reports have shown that survival remains unchanged (Fisher et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical extent and level of axillary dissection has also been discussed extensively, with some showing preference for complete axillary clearance (Fentiman and Mansel, 1991) and others opting for partial dissection and sampling of four lymph nodes (Steele et al, 1985;Greenall, 1995). The latter approach, however, runs the risk of failing to accurately stage the patient, with error rates as high as 24% (Kissin et al, 1982;Kjaergaard et al, 1985).…”
mentioning
confidence: 99%